Design of small-scale tilt-rotor unmanned aerial vehicle - Kassymov, A.; Orazbayev, D.; Akhatova, A.; Adair, D.; Ali, Md. H. (Nazarbayev University, 2014)
Unmanned Aerial Vehicle (UAV) is the aircraft without a human pilot aboard. UAVs are subcategorized as RC Models, which are controlled by a pilot via transmitter-receiver system, and Drones, which are fully autonomous. They are used for different military missions, such as surveillance and reconnaissance. They are widening their use in civil areas, for example, search and rescue operations, filmmaking, remote sensing of chemical leaks, crop spraying and monitoring in agriculture, etc. Most of the UAVs are either of airplane (fixed-wing) type or copter (Vertical Take Off and Landing) type. The aim of this project is to design the UAV that will combine the hovering abilities of multicopters with the endurance of fixed-wing aircrafts.
Keywords: prototype model; design; tilt-rotor; unmanned aerial vehicle